INTEGRATING ESG AND SUSTAINABILITY IN THE RAW MATERIALS SECTOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The global demand for raw materials continues to grow, intensifying the need for responsible mining practices that balance economic growth with environmental stewardship and social responsibility. This paper explores the integration of Environmental, Social, and Governance (ESG) principles into sustainable mining practices, highlighting their critical role in reshaping the industry’s future. Focusing on case studies and industry trends, the research examines how mining companies are adopting ESG frameworks to minimize environmental impact, enhance community engagement, and promote transparent governance. The paper also analyses findings on the financial and operational benefits of ESG integration, including risk mitigation, improved stakeholder trust, and long-term value creation. By aligning business goals with sustainable development objectives, mining companies can enhance their social license to operate and remain competitive in a rapidly evolving market. The findings underscore the importance of a holistic approach to responsible mining, advocating for collaborative efforts among industry stakeholders, policymakers, and communities.